Evaluasi Efektivitas Strategi Destination Branding Terhadap Citra Destinasi dan Keputusan Pembelian Paket Wisata: (Studi Komparatif Destinasi Wisata Alam vs Wisata Buatan Menggunakan Analisis Regresi Berganda) - Anthoneta Telsy Waelauruw; Evandro Adolf Manuputty (P3M Politeknik Negeri Ambon, 2025)
The global tourism industry faces significant transformation in the digitalization era, where destination branding strategies become crucial instruments for building competitive tourism destination positioning. This phenomenon creates urgency to understand the effectiveness of specific branding approaches between natural and artificial tourism destinations. This research aims to analyze the effectiveness of destination branding strategies in forming destination image, evaluate the influence of destination image on tour package purchase decisions, and compare variable relationships in both destination types. The study employs a quantitative approach with comparative study design involving 25 respondents (13 natural tourism, 12 artificial tourism) through structured questionnaires using Likert scale 1-5 and multiple regression analysis using SPSS. Results show relatively equal branding strategy effectiveness with scores of 3.01 (natural tourism) and 2.97 (artificial tourism). Natural tourism destinations excel in brand communication (3.23), while artificial tourism is stronger in brand positioning (3.23) and brand identity (2.96). Paradoxical findings reveal artificial tourism destinations have more positive image (3.05) but lower purchase decisions (2.61) compared to natural tourism (2.81 and 2.69). Correlation analysis shows different patterns with natural destinations showing negative correlation between branding strategy-destination image (-0.378), while artificial tourism correlates positively (0.170). The research concludes the necessity of differentiation approaches in destination branding: natural destinations require organic-community driven strategies, while artificial destinations need structured-technology driven approaches.Keywords: Destination Branding, Destination Image, Multiple Regression, Natural Tourism, Purchase Decision